Monosomes buffer translational stress to allow for active ribosome elongation - Schieweck, Rico; Ciccopiedi, Giuliana; Klau, Kenneth; Popper, Bastian (Frontiers in Molecular Biosciences, 2023)
The synthesis of proteins is a fundamental process in the life-span of all cells. The activation of ribosomes on transcripts is the starting signal for elongation and, in turn, the translation of an mRNA. Thereby, most mRNAs circulate between single (monosomes) and multi ribosomal (polysomes) particles, a process that defines their translational activity. The interplay between monosomes and polysomes is thought to crucially impact translation rate. How monosomes and polysomes are balanced during stress remains, however, elusive. Here, we set out to investigate the monosome and polysome levels as well as their kinetics under different translational stress conditions including mTOR inhibition, downregulation of the eukaryotic elongation factor 2 (eEF2) and amino acid depletion. By using a timed ribosome runoff approach in combination with polysome profiling, we found that the used translational stressors show very distinct effects on translation. However, they all had in common that the activity of monosomes were preferentially affected. This adaptation seems to be needed for sufficient translation elongation. Even under harsh conditions such as amino acid starvation, we detected active polysomes while monosomes were mostly inactive. Hence, it is plausible that cells compensate the reduced availability of essential factors during stress by adapting the levels of active monosomes to favor sufficient elongation. These results suggest that monosome and polysomes levels are balanced under stress conditions. Together, our data argue for the existence of translational plasticity that ensure sufficient protein synthesis under stress conditions, a process that is necessary for cell survival and recovery.